2014
DOI: 10.1590/1677-3225v13n2a11
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in inland Brazilian adolescents and its relationship with social determinants

Abstract: Aim: To identify the prevalence of dental caries in inland Brazilian adolescents, and to analyze the influence of socio-demographic and clinical variables, and access to dental service on caries experience. Methods: This study had a non-probabilistic sample comprising 504 adolescents aged 12 years, attending public schools in the city of Nova Friburgo, mountain region of Rio de Janeiro, Brazil. The World Health Organization (WHO, 1997) criterion was used by previously calibrated examiners to report dental cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 16 publications
1
13
1
4
Order By: Relevance
“…This study showed results in contrast with those of Anders and Davis with respect to the prevalence of caries, because when the results of this study are compared with those of the national epidemiological survey, the DMF‐T measurements of individuals with ID were observed to be higher for the age groups of 12 (CPO‐D = 5.05) and 15 to 19 years of age (DMF‐T 7.89), compared with those of 2.07 and 4.25, respectively, referring to the population in general. Moreover, in this study, the mean DMF‐T (5.05) at 12 years of age was found to be higher than the value found in the epidemiological survey conducted in 2012 (DMF‐T = 1.90) in the municipality of Nova Friburgo/RJ, Brazil …”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This study showed results in contrast with those of Anders and Davis with respect to the prevalence of caries, because when the results of this study are compared with those of the national epidemiological survey, the DMF‐T measurements of individuals with ID were observed to be higher for the age groups of 12 (CPO‐D = 5.05) and 15 to 19 years of age (DMF‐T 7.89), compared with those of 2.07 and 4.25, respectively, referring to the population in general. Moreover, in this study, the mean DMF‐T (5.05) at 12 years of age was found to be higher than the value found in the epidemiological survey conducted in 2012 (DMF‐T = 1.90) in the municipality of Nova Friburgo/RJ, Brazil …”
Section: Discussioncontrasting
confidence: 84%
“…QoL was considered the dependent variable (dichotomized by the median at 16 points: ≤16 and >16) . All the independent variables were dichotomized, as follows: sex (female and male), age (11 to 19 years and 20 to 29 years), income (≤3 minimum wages and >3 minimum wages), schooling/educational level (≤8 years of schooling and >8 years of schooling), DMF‐T (0 and >0), need for dental prosthesis (no and yes), gingival bleeding (absence and presence), periodontal pocket (absence and presence [>3 mm]), dental treatment need (no and yes), toothache in the last 6 months (no and yes), visit to the dentist (no and yes), sugar consumption/day (≤4 times/day and >4 times/day), frequency of tooth brushing/day (≤2 times/day and >2 times/day), material support (dichotomized by the median: ≤13 and >13), information support (dichotomized by the median: ≤15 and >15), social support of positive social interaction (dichotomized by the median: ≤12 and >12). The Chi‐square or Exact Fisher test was used to test the association of the independent variables with the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Crude and adjusted analyses were performed to test the associations between the dependent variable, OHRQoL (CPQ 11-14 ), dichotomised by the median (CPQ ≤ 18 and CPQ > 18), and the independent sociodemographic, clinical, and SHP access variables, which were dichotomised following Assaf et al, 18 as previously described. The variables with p < 0.20 in the crude analyses were tested in the multiple logistic regression model, with the criterion of permanence in the final model set at p ≤ 0.10.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it should be emphasised that educational interventions in oral health apart from other health actions and with fragmented approaches that separate the oral cavity from general health have been criticised because they are limited in ensuring a permanent transformation in individuals, or even in reducing health inequalities. 2,18 In addition to the factors mentioned above, it is possible to highlight the absence of a strategy of continuing education in health between the teachers and the primary care professionals that will be a part of adolescents' day-to-day life. Thus, it is necessary for the students to be motivated and the teachers trained so that the concept of oral health promotion is an integral part of school life, ensuring that the information and healthy habits acquired are applied continuously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation